First Measurements of Low‐Frequency Sferics Associated With Terrestrial Gamma‐Ray Flashes Produced by Equatorial Thunderstorms. Issue 17 (2nd September 2020) - Zhang, Hongbo; Lu, Gaopeng; Lyu, Fanchao; Ahmad, Mohd Riduan; Qie, Xiushu; Cummer, Steven A.; Xiong, Shaolin; Briggs, Michael S.
Abstract: The low‐frequency (LF) lightning sferics associated with terrestrial gamma‐ray flashes (TGFs) detected by Fermi Gamma‐ray Burst Monitor over equatorial thunderstorms have been recorded at a station in Melaka, Malaysia, since 2017. We examine the LF sferics of two Fermi TGFs, including one TGF‐associated lightning discharge at only about 28 km range. Both TGFs are related to the strongest pulse during the initial stage of their parent intracloud (IC) lightning, while in both cases, the light curve of gamma‐ray photon lags the major lightning pulse by approximately 100 μs. TGF occurred about 3 ms after the lightning initiation when the initial upward negative leader has ascended for about 2 km to reach the height of 10–11 km. Our analyses on a statistical basis show that TGF‐related lightning is mostly located in the strong convection of equatorial thunderstorms at the mature stage, and nearly half TGFs are not produced in the strongest convection region. Plain Language Summary: As one of the effects caused by tropospheric lightning in the near‐Earth space, terrestrial gamma‐ray flashes (TGFs) have been registered as worldwide phenomenon typically associated with deep convection of thunderstorms. Although the equatorial regions appear to be one of the hot spots for the spaceborne observations of TGFs, the ground‐based measurements of TGF‐associated lightning sferics have not been conducted so far near equator. Since the summer of 2017, a low‐frequency (LF) magnetic field sensor has been installed on the campus of Universiti Teknikal Malaysia Melaka to record the radio frequency lightning signal associated with TGFs detected by Fermi. Due to the apparent proximity to the active region of TGF observations, the TGF‐associated lightning signals have been recorded within 200 km for several cases during 2 year operation, including one recorded at a distance as close as 28 km. For another case with TGF‐associated sferics recorded at 270 km range, the progression of negative upward leader can be tracked by examining the sequence of lightning pulses along with their ionospheric reflection. Through individual analysis and statistical research, the types, stages of TGF‐related thunderstorms, and the positions of lightning source relative to storms are discussed in this paper. Key Points: Radio frequency lightning sferics associated with TGFs are measured at range as close as about 28 km with respect to equatorial thunderstorms Parent lightning of TGFs in the equatorial area bears the similar progressing features and height of thundercloud top to those at higher latitudes Nearly half TGFs are located in the strong but not the strongest convection region of varied‐scale equatorial thunderstorms at the mature stage